Reading tourism texts a multimodal analysis - Francesconi, Sabrina, 1976- (Tourism and cultural change, 2014)
This volume explores the relationship between tourism and travel texts and contemporary society, and how each is shaped by the other. A multimodal analysis is used to look at a variety of texts including novels, travel brochures, blogs and videos.